Synergism in Two-Component Insecticides with Dillapiole against Fall Armyworm - Murilo Fazolin; Humberto R. Bizzo; André F. M. Monteiro; Maria E. C. Lima; Natália S. Maisforte; Paola E. Gama (Plants, 2023)
The fall armyworm (Spodoptera frugiperda), a polyphagous insect pest, is a major threat to food production, rapidly spreading through all the tropical areas in the world. Resistance has developed to the control protocols used so far (pyrethroids, organophosphorus, and genetically modified plants), and alternative strategies must be found. The bioactivity in essential oils is usually associated with the major constituents, but synergistic interactions among the constituents (even minor ones) can improve the levels of activity considerably. Herein, we tested the insecticidal activity of several constituents of the essential oil from Piper aduncum, an Amazonian Piperaceae, both separately and as binary mixtures, through their application on the dorsal side of the larva pronotum. Dillapiole proved to be, isolated, the most active compound in this oil (LD50 = 0.35 ppm). In binary mixtures, a strong synergistic effect was observed for the pairs of dillapiole with β-caryophyllene (LD50 = 0.03 ppm), methyl eugenol (LD50 = 0.05 ppm), and α-humulene (LD50 = 0.05 ppm). In some cases, however, antagonism was recorded, as for dillapiole + β-pinene (LD50 = 0.44 ppm). The use of binary mixtures of essential oil constituents as low-environmental-toxicity insecticides allows a fine tuning of the insecticidal activity, and the exploitation of synergy effects.